MODIFIKASI IRC3 (INTRODUCE, REVIEW, COMPARE, CONCLUSION, CREATIVE) DI IAI Al-MAWADDAH WARRAHMAH KOLAKA - Nur Thahirah Umajjah Irha (INSTITUT AGAMA ISLAM NEGERI PONTIANAK, 2019)
IAI Al-Mawaddah Warrahmah Kolaka is one of the PTKIS (private Islamic college) in the Kolaka district, which shows an increase in the number of students each year, so the learning system needs to improve to produce qualified alumni. This study aims to determine the application and results of the IRC3 Modified Research-Based Learning Model (Introduce, Review, Compare, Conclusion, and Creative) in Kolaka's IAI Al-Mawaddah Warrahmah in terms of student responses. This research was conducted for 4 months in the fourth semester students of the PAI Department of learning media courses. The type of research used is descriptive research. The conclusions from the results of this study indicate that the application of IRC3 modification research based learning in Kolaka IAI Al Mawaddah Warrahmah is done in 5 Steps, namely: (Introduce, Review, Compare, Conclusion, Creative) and the final result of implementing this learning model is the student's creative work in the form of research journals. The application of IRC3 modification research based learning models received positive responses from all students. [IAI Al-Mawaddah Warrahmah Kolaka adalah salah satu PTKIS di wilayah kabupaten Kolaka, yang menunjukkan peningkatan jumlah mahasiswa di tiap tahunnya, sehingga sistem pembelajaran perlu diperhitungkan untuk menghasilkan alumni yang unggul dalam kualitas. Penelitian ini bertujuan untuk mengetahui penerapan dan hasil atas Model Pembelajaran Berbasis Riset Modifikasi IRC3 (Introduce, Review, Compare, Conclusion, Creative) di IAI Al-Mawaddah Warrahmah Kolaka ditinjau dari respon mahasiswa. Penelitian ini dilakukan selama 4 bulan pada mahasiswa semester IV Jurusan PAI mata kuliah media pembelajaran. Jenis penelitian yang digunakan adalah penelitian deskriptif. Kesimpulan dari hasil penelitian ini menunjukkan bahwa penerapan pembelajaran berbasis riset modifikasi IRC3 di IAI Al Mawaddah Warrahmah Kolaka dilakukan dengan 5 Langkah yaitu: (Introduce, Review, Compare, Conclusion, Creative) dan hasil akhir dari penerapan model pembelajaran ini adalah karya kreatifitas mahasiswa yang dituangkan dalam bentuk jurnal hasil penelitian. Penerapan model pembelajaran berbasis riset modifikasi IRC3 mendapat tanggapan positif dari seluruh mahasiswa]. Kata Kunci: Pembelajaran berbasis riset; Modifikasi IRC3; IAI Kolaka